DEVELOPMENT OF AUGMENTED REALITY IN UNDERSTANDING THE NETS AND RIBS OF SPATIAL BUILDINGS - Sondang Purnamasari Pakpahan; Andy Sapta; Uliya Khoirun Nisa (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Technology-based learning media is currently widely developed in accordance with the 21st-century learning model. Many subject matters are better delivered when using technology-based media. One of the media that can be used is Augmented Reality. Based on this, the purpose of this study is to develop Augmented Reality in conveying the material of nets and ribs in Build Space. Augmented Reality is developed using 3D modeling, rigging, and animating methods, which are then combined using Unity. The results of the development of Augmented Reality applications in understanding the nets and ribs of this building space have been validated by experts and users. The validation results of this Augmented Reality application are rated Very Good.Keywords: augmented reality; nets; ribs; spatial building. Abstrak: Media pembelajaran berbasis teknologi saat ini banyak dikembangkan sesuai dengan model pembelajaran abad 21. Banyak materi pelajaran yang lebih baik disampaikan bila menggunakan media berbasis teknologi. Salah satu media yang dapat digunakan adalah Augmented Reality. Berdasarkan hal tersebut, tujuan penelitian ini adalah untuk mengembangkan Augmented Reality dalam menyampaikan materi jaring-jaring dan rusuk pada Bangun Ruang. Augmented Reality ini dikembangkan dengan menggunakan metode 3D modeling, rigging dan animating, yang selanjutnya digabungkan dengan menggunakan Unity. Hasil pengembangan aplikasi Augmented Reality dalam memahami jaring-jaring dan rusuk dari bangun ruang ini telah divalidasi oleh ahli dan user. Hasil validasi aplikasi Augmented Reality ini dinilai Sangat Baik.Kata kunci: augmented reality; bangun ruang; jaring-jaring; rusuk